Correlation of subtraction parathyroid scintigraphy with weight, pathohistologic finding and oxyphil cell content of parathyroid glands in parathyroid hyperplasia - Dugonjić Sanja; Cerović Snežana; Janković Zoran; Ajdinović Boris (Vojnosanitetski Pregled)
Background/Aim. Parathyroid hyperplasia (PHP) is defined as an absolute increase in the mass of parenchymal cells of the parathyroid gland. PHP is classified as primary, secondary and tertiary. The enlargement of parathyroid glands (PG) is usually asymmetric, resulting in a “dominant“ gland. In order to confirm the diagnosis, at least two glands should be examined histologically. Subtotal parathyroidectomy, i.e. removal of the three PG and leaving a small remnant of the forth, is the treatment of choice. High percent of PHP recurrence imposes the need for preoperative high sensitivity localizing procedures. Parathyroid scintigraphy localizes about 60% of hyperplastic glands. The aim of this study was to correlate findings of subtraction parathyroid scintigraphy (SPS) with weight, pathohistologic finding and oxyphil cell (OC) content of PG in patients with primary, secondary and tertiary parathyroid hyperplasia. Methods. Twenty-seven patients with primary/secondary PHP underwent SPS before surgery. Scintigraphic results were graded from 1-5, in relation to the degree of uptake. SPS graded 3, 4 and 5 were considered positive. The number and weight of operated PG were evaluated macroscopically. Pathohistologic and cellular types were defined on standard stained hematoxylin-eosin slides. OC content was defined as a percent of OC and graded from 1 to 3: grade 1 < 10%, grade 2 ≥ 10% and grade 3 ≥ 20% of OC. Results. SPS localized dominant gland in all patients with sensitivity 100%, and 51 from 73 hyperplastic PG, with sensitivity per gland of 70%. PG weighed 0.1 g to 6.7 g (median 1 g). A significant positive correlation (p < 0.0001) was found between the SPS results and PG weight. A significant positive correlation was found between PG weight and OC content (p = 0.0002). An insignificant correlation was found between SPS and OC content. Thirty-eight PG had < 10% of OC, 32 PG had < 10% and 3 PG had ≥ 20% of OC. Four patients had diffuse PHP and 23 patients nodular PHP. There was no statistically significant difference in SPS results compared to hyperplasia type, and between OC content and hyperplasia type. A significant positive correlation (p = 0.05) was found between PG weight and hyperplasia type. Conclusion. A high positive correlation was found between SPS results and PG weight, PG weight and OC content and PG weight and hyperplasia type. Between SPS results and OC content, and between SPS results and hyperplasia type, an insignificant correlation was found. Our results showed that SPS is a reliable and very sensitive diagnostic tool in detecting abnormal PG in parathyroid hyperplasia, reaching 100% sensitivity in detecting a “dominant gland” and sensitivity per localized gland of 70%. Causes that affect increased uptake of liposolubile Tc99m radiopharmaceuticals (RF) in the hyperfunctional PG tissue and conditions which prevent RF admission into the PG cells still remain to be accurately and precisely determined.